Application of SMART, TOPSIS, and VIKOR Systems in Joint Admission Control - Alkhawlani, Mohammed M. (Blue Eyes Intelligence Engineering and Sciences Publication (BEIESP), 2015)
Joint Admission Control (JAC) handles the admis-sion of all new or handoff service requests in the mod-ern heterogeneous networks and allocates the required resources and guarantees the QoS constraints for the service. JAC is a multicriteria problem in nature, and the usage of MCDM system is mandatory to decrease the influence of the dissimilar, imprecise, and contra-dictory measurements for the JAC criteria coming from different sources. In this paper, three different decision support systems are developed to address the JAC problem in the modern heterogeneous networks. These systems use SMART, TOPSIS, and VIKOR MCDM methods. Illustrative numerical examples for the devel-oped systems are presented. The examples show that the choice of the MCDM tool can directly affect the ranking order of the available access networks, and hence, the selection of the MCDM methods is highly critical in any JAC solution.